THE TRADITION OF SPOILING VESSELS: ORIGINS ACCORDING TO THE ARCHEOLOGICAL DATA OF CISCAUCASIA - Korenevskij, Sergej Nikolaevic (History, Archeology and Ethnography of the Caucasus, 2021)
The article reviews the deformed metallic and ceramic vessels of the Maikop-Novosvobodnenskaya community. The study is mainly based on the author’s photographs and sketches, stored in the State Hermitage Museum. The artifacts themselves were published numerous times, but the deformation of vessels, in particular, has not yet been covered. The revealed defects allow us to conclude that some of the vessels of the Maikop Kurgan were damaged intentionally; prior to placing the vessels into the grave, some of them could have been repaired. Of particular interest is a bronze bucket found in the Maikop Kurgan: its hinges for mounting the arched handles were purposely broken, i.e. the bucket was placed in the grave in the “murdered” state. The article analyzes all known shapes of bronze vessels from the whole assemblage of the Maikop-Novosvobodnenskaya community and its periphery. It has been revealed that all of them have some forms of defects or traces of repair. In most cases they are not suitable for household use, which is the very feature of the tradition of placing them in graves. Damage or repair of metallic vessels or spoilage of pottery could have been considered as a possibility for using the damaged vessels by the kinsman in the “land of ancestors”, and an individual fragment of a vessel acquired magical properties. The origins of spoiling vessels and the use of individual shreds in funerary rites has its roots in funerary rites of the Proto-Yamnaya culture of the Pre-Maikop period of Ciscaucasia. Thus, we believe that this tradition was borrowed by the bearers of the Maikop culture from their predecessors. Subsequently, it was passed to the tribes of the Middle Bronze Age.